Amanat Agung sebagai Tugas Misi: Apa dan Siapa yang Ditugaskan - Baginda Sitompul; Tomson Sihol Sianturi; Jefpri Sihombing; Riki Toni Situmeang; Dantoni Manalu (LPPM - STT Kadesi Bogor, 2024)
The Great Commission was the last message that gave by Jesus to His disciples before His ascension to heaven. It is an absolute command that must do by all believers who have faith in Christ. It also must be a cornerstone for evangelical activity. Goal of the great commission's activity is to share that salvation has provided in Jesus so since that is also God's grace and love it can be felt by everyone who give response and believe. To have a correct understanding so that capable to get the conclusion based on the truth, observation using exegetical method according to excavation from the original language could be support the discovery. The main purpose of Great Commission is